Four-rod Instrumentation for Treatment of Charcot Spinal Arthropathy Causing Autonomic Dysreflexia: Case Report and Literature Review - Zyck, Stephanie (Cureus, 2016)
Late complications of spinal cord injury can include Charcot arthropathy, in which spinal instability occurs as a result of repetitive trauma in the insensate spine. In rare cases, this can present as autonomic dysreflexia. We present the case of a 60-year-old man with longstanding C6 quadriplegia who presented with six months of hypertension, diaphoresis and dizziness. After an extensive workup, the patient's symptoms were attributed to autonomic dysreflexia in the setting of spinal instability from Charcot spinal arthropathy. Computed tomography (CT) and magnetic resonance imaging (MRI) revealed instability with degenerative changes at L1-L2. We present our case with a literature review to discuss management of this uncommon situation. The patient underwent posterior fusion and instrumentation from T8-L5 with four rods, alternating screws and crosslinks with a good reduction and solid stabilization of the spine. Postoperatively, the patient experienced immediate relief of all symptoms. Our case demonstrates effective surgical treatment for Charcot spinal arthropathy causing autonomic dysreflexia. Stabilization with instrumentation and fusion of underlying Charcot spinal arthropathy removed the trigger of the autonomic dysreflexia and alleviated our patient's symptoms.